Internet of Things-Based Entrepreneurship Lockers - Yulius Bisma Cahyaprawira; Andre Kurniawan Pamudji; Tecla Brenda Chandrawati; Erdhi Widyarto Nugroho (Soegijapranata Catholic University, 2022)
The development of the internet, which was originally only a medium of communication, is now more varied and sophisticated. An example of the development of the internet is Internet Of Things (IoT) , which in this study will discuss the implementation of IoT. As a form of pandemic recovery for IoT entrepreneurial activities, researchers developed lockers that can help entrepreneurial actors (especially on campus) to get up during the recovery period from the pandemic. The general concept of this locker is that the seller puts his merchandise into the locker and the buyer will pick it up by paying through QRIS. In other words, this locker provides convenience in transactions because it is done cashless. The design begins with making the work steps and logic flow of the locker which then makes the circuit scheme of the hardware. The hardware circuits used have their respective roles and support each other. This research hopes that with the IoT-based entrepreneurial lockers, it is expected not only to help partners / entrepreneurial actors on campus, but also attract new partners and encourage campus residents to dare to be entrepreneurs.